Modifikasi Start Block Untuk Pembelajaran Atletik Lari Sprint (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to produce a modified starting block for the development of learning athletics sprints for Elementary School students Bintoro 2 Demak. This study uses a model of development which refers to the development of Borg & Gall.The data analysis technique used is descriptive percentages. From the test results obtained by a small group of expert evaluation data, namely, expert penjas 95% (very good), a study 92.5% (excellent), the average results of the questionnaire on a small group of test results obtained 86% (good). The average yield at the end of the questionnaire test results obtained large group 93.2% (very good).Conclusion that the model of development of modified starting blocks for sprinting athletics lessons forelementary students Bintoro N 2 Demak deserves used to study athletic training run for the Sprint andelementary school athletes.